2003
DOI: 10.1007/3-540-45068-8_60
|View full text |Cite
|
Sign up to set email alerts
|

A Browser Compatibility Testing Method Based on Combinatorial Testing

Abstract: Abstract. For ensuring the displaying effects of Web applications, it is important to perform compatibility testing for browsers under the different configurations and it is a hard task to test all. So this paper focused on the improvements for browser compatibility testing. Firstly, we introduced the related work. Then we analysed the functional speciality of the current popular browsers, and provided the preconditions to simplify problems. Next we gave an instance and brought forward the single factor coveri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 9 publications
(8 reference statements)
1
14
0
1
Order By: Relevance
“…Since 2003, we have done much work in the test case generation [Nie et al , 2006a[Nie et al , 2006bWang et al 2007Wang et al , 2008, fault location ] and the application of CT [Xu et al 2003a[Xu et al , 2003b. In this article we propose a complete theory of the Minimal Failure-causing Schema (MFS) first.…”
Section: Introductionmentioning
confidence: 93%
“…Since 2003, we have done much work in the test case generation [Nie et al , 2006a[Nie et al , 2006bWang et al 2007Wang et al , 2008, fault location ] and the application of CT [Xu et al 2003a[Xu et al , 2003b. In this article we propose a complete theory of the Minimal Failure-causing Schema (MFS) first.…”
Section: Introductionmentioning
confidence: 93%
“…Several empirical studies of combinatorial testing have been reported that applied combinatorial testing on major features of a mobile phone application testing [18], an email system testing [19], satellite communications system testing [22], configuration testing [23], browser compatibility testing [24], network interface testing [25], and protocol testing [26]. The studies show that combinatorial testing is very effective and can be applied to a wide variety of applications.…”
Section: Related Workmentioning
confidence: 99%
“…QA strategies for evaluating web portability include launching web applications in varied configurations [3,4,8,9,54], looking for unsupported HTML in source code [6,16], and attempting to transform code into a form that is universally supported [11]. This section outlines existing approaches along with their limitations and tools that implement them.…”
Section: Web Portability Analysismentioning
confidence: 99%